Z dziejów polonistyki szkolnej. Stypendyści Towarzystwa Pomocy Naukowej dla Młodzieży Prus Zachodnich o polskich pisarzach romantycznych = From the history of polish studies at school. The students granted scholarship of the Association for Promoting the Studies of the Youth of West Prussia on Polish romantic writers - Kulka, Bronisława (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The Society for Educational Aid to the Youth of Western Prussia was active since 1848 ti1l 1920. Its aim was to give financial help to the young Polish learners who were to become the inteligentsia and the professional craft in the future. Those who were helped by the Society were obliged to make satisfactory progress in learning as well as to master the Polish and the German language
Keywords: Towarzystwo Pomocy Naukowej dla Młodzieży Prus Zachodnich; język polski - nauczanie